Analysis and Optimization of Machining Process of Thin-wall Gear Ring of Planetary Reducer - Bin Liu; Lilin Wei; Haodong Yang; Changfeng Yan; Fuqiang Ren; Wei Luo (Jixie chuandong)
Aiming at the requirements of large radial size， large load-bearing load and high precision of the thin-walled gear ring of a planetary reducer for a high-altitude rescue vehicle， the deformation of the thin-walled gear ring during processing and heat treatment is analyzed， and the cause of the deformation of the workpiece is found. A solution is developed， the process route of thin-walled ring gear processing and heat treatment is optimized. By using Deform heat treatment simulation software， the optimized heat treatment route is simulated， and the feasibility of the optimized scheme is verified. This optimization scheme improves the accuracy of the workpiece， meets the requirements of a certain high-altitude rescue vehicle planetary reducer to work normally under complex working conditions， and ensures the safe and stable operation of mechanical equipment. Engineering practice shows that this optimization scheme is suitable for low-speed and heavy-duty high-altitude rescue vehicle slewing mechanism reducer， and has high economic and practicality.